2018
DOI: 10.3892/ol.2018.8040
|View full text |Cite
|
Sign up to set email alerts
|

Transformation to small‑cell lung cancer following treatment with icotinib in a patient with lung adenocarcinoma

Abstract: Abstract. The present study describes the case of a 48-year-old man who was diagnosed with lung adenocarcinoma with an epidermal growth factor receptor (EGFR) 21 L858R mutation. The patient received surgery and adjuvant chemotherapy. When multiple lung metastases appeared, icotinib was administered. Following resistance to icotinib, biopsy by endobroncheal ultrasonography for a right lung hilar lymph node revealed transformation to a neuroendocrine morphology. Neuron-specific enolase (NSE) levels were elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…These pressures may also cause histologic changes and tumor cells settle in other organs in a changed histology. Histologic change from AdenoCa to SCC after surgery and adjuvant therapy has been previously described [ 17 ]. One patient (case 3) in our study is interesting because the diagnosis of primary lung cancer and its brain metastasis was confirmed by surgical resection, and both were pure AdenoCa and SCC, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These pressures may also cause histologic changes and tumor cells settle in other organs in a changed histology. Histologic change from AdenoCa to SCC after surgery and adjuvant therapy has been previously described [ 17 ]. One patient (case 3) in our study is interesting because the diagnosis of primary lung cancer and its brain metastasis was confirmed by surgical resection, and both were pure AdenoCa and SCC, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Gu et al [ 24 ] also reported that serum ProGRP and NSE levels were markedly elevated compared with normal levels when SCLC transformation occurred. In addition, many other literature reports have shown a significant increase in NSE levels, indicating SCLC or LCNEC transformation[ 11 , 18 , 32 , 33 ]. In our cases, NSE levels were detected in six cases at the time of SCLC transformation.…”
Section: Discussionmentioning
confidence: 99%
“…SCLC transformation is 1 resistance mechanism associated with first-generation EGFR-TKIs, and is more frequent in lung adenocarcinomas with EGFR-activating mutations than in EGFR wild-type tumors [7–9] . A number of mechanisms of acquired resistance to EGFR-TKI therapy in EGFR-mutant lung adenocarcinoma have been described, including the EGFR T790M mutation, EGFR amplification, MET gene amplification, PIK3CA mutation, and transformation to SCLC [10,11] . However, the potential mechanism underlying SCLC phenotype conversion after TKI therapy remains unclear.…”
Section: Discussionmentioning
confidence: 99%